The Relationship between Advertising and Sales for Selected Consumer Goods - Agatep, Myra Vina D. (Philippine Management Review; Vol 10 (2002), 2016)
This paper examines the normally taken-for-granted reciprocal relationship between advertising and sales utilizing data from three types of Philippine consumer goods. “Excessiveness” of advertising expenditures is also explored by comparing optimal and actual industry advertising intensity ratios.  Results reveal that the relationship is not reciprocal:  advertising positively influences firms’ sales but sales do not influence advertising.  Furthermore, results on the test of excessiveness of advertising expenditures show that Philippine companies need to advertise more